Changes in the place of death for older adults with cancer: Reason to celebrate or a risk for unintended disparities?. Issue 3 (April 2021) - Sedhom, Ramy; Kuo, Pei-Lun; Gupta, Arjun; Smith, Thomas J.; Chino, Fumiko; Carducci, Michael A.; Bandeen-Roche, Karen
Abstract: Background: Place of death is important to patients and caregivers, and often a surrogate measure of health care disparities. While recent trends in place of death suggest an increased frequency of dying at home, data is largely unknown for older adults with cancer. Methods: Deidentified death certificate data were obtained via the National Center for Health Statistics. All lung, colon, prostate, breast, and pancreas cancer deaths for older adults (defined as >65 years of age) from 2003 to 2017 were included. Multinomial logistic regression was used to test for differences in place of death associated with sociodemographic variables. Results: From 2003 through 2017, a total of 3, 182, 707 older adults died from lung, colon, breast, prostate and pancreas cancer. During this time, hospital and nursing home deaths decreased, and the rate of home and hospice facility deaths increased (all p < 0.001). In multivariable regression, all assessed variables were found to be associated with place of death. Overall, older age was associated with increased risk of nursing facility death versus home death. Black patients were more likely to experience hospital death (OR 1.7) and Hispanic ethnicity had lower odds of death in a nursing facility (OR 0.55). Since 2003, deaths in hospice facilities rapidly increased by 15%. Conclusion: Hospital and nursing facility cancer deaths among older adults with cancer decreased since 2003, while deaths at home and hospice facilities increased. Differences in place of death were noted for non-white patients and older adults of advanced age.